Pengembangan Alat Monitoring Suhu Multisensor Berbasis Mikrokontroler - Efendi, Rustam; Tando, Arjal; Padang, Welly; Aries, Mulhin; Herlina, Herlina (Jurnal Teknik Mesin Indonesia, 2024)
one Adafruit MCP9808 sensor and five Adafruit MAX31856 thermocouple amplifiers. The design of this data logger allows temperature measurement in various applications, with a focus on monitoring room temperature. The prototype can be used in experiments, research, and industrial applications that require accurate temperature monitoring. This temperature data logger has the potential for wide-ranging applications in various contexts, with advantages in flexibility and affordability. The research validates that the MCP9808 sensor and MAX31856 amplifiers have a high level of accuracy in temperature measurements. The results of temperature measurements in a room environment indicated a temperature of approximately 29 ℃. This data logger design serves as a robust alternative for researchers who face limitations in acquiring standard commercial data loggers. The prototype has the potential to be a valuable tool in experiments and scientific research in various applications that demand precise temperature monitoring.